A combined wall and roof solar chimney in one building. (1st February 2022) - Wang, Qingyuan; Zhang, Guomin; Wu, Qihong; Li, Wenyuan; Shi, Long
Abstract: Although a combination of various (or types of) solar chimneys (SCs) can overcome the limitations of a solo system, the interactions, designing factors and overall performance in one building are still not known. Therefore, a combined wall and roof SCs were investigated both numerically and theoretically through this study. After being coupled with a roof SC, the performance of the wall SC is generally enhanced, which is quite stable when the designs of the roof solar chimney keep changing. The optimal designs of the wall SC are basically the same with those without coupling a roof SC. Furthermore, the window area shows an obvious impact on the roof SC but not the wall SC. Solar radiation offers an obviously positive effect on both the wall SC and the overall performance, while its impacts on the roof SC are relatively less obvious. The optimized design of the combined system can be achieved with specific designs, such as possibly big absorption walls for both chimneys, a big window, an appropriate level of cavity gap and air inlet height for the wall SC, a relatively small cavity gap for the roof SC, and a closer wall and roof SCs. A theoretical model is also developed to predict the airflow rates through both the wall and roof SCs. A coefficient, namely α, is proposed to describe the percentage of the airflow from the window to the wall SC. The predictions based on fixed α obey well with those numerical results. Highlights: Interaction between wall and roof solar chimneys (SCs) in a building is addressed. Airflow bifurcation from the window to different chimney cavities is studied. The impacts from the main influencing factors on SCs' performance were addressed. Theoretical model is developed to predict the performance of both wall and roof SCs. About 72% of the incoming airflow from the window enter the wall solar chimney.